2000
DOI: 10.1007/s002320001055
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Protein Tyrosine Kinase in Osmoregulation of Na + Transport and Membrane Capacitance in Renal A6 Cells

Abstract: Renal A6 cells have been reported in which hyposmolality stimulates Na(+) transport by increasing the number of conducting amiloride-sensitive 4-pS Na(+) channels at the apical membrane. To study a possible role of protein tyrosine kinase (PTK) in the hyposmolality-induced signaling, we investigated effects of PTK inhibitors on the hyposmolality-induced Na(+) transport in A6 cells. Tyrphostin A23 (a PTK inhibitor) blocked the stimulatory action of hyposmolality on a number of the conducting Na(+) channels. Tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…No differences were discernible between cells from different passages. Cells were maintained in plastic tissue culture flasks at 27°C in a humidified incubator with 1% CO 2 in air in a culture medium, which contained 75% (volume / volume (v/v)) NCTC-109 medium (GIBCO, Grand Island, NY, U.S.A.), 15% (v/v) distilled water and 10% (v/v) fetal bovine serum (GIBCO) (17,20,23,24). The normal solution contained (in mM) 120 NaCl, 3.5 KCl, 1 CaCl 2 , 1 MgCl 2 , and 10 HEPES adjusted to pH 7.4 with NaOH.…”
mentioning
confidence: 99%
“…No differences were discernible between cells from different passages. Cells were maintained in plastic tissue culture flasks at 27°C in a humidified incubator with 1% CO 2 in air in a culture medium, which contained 75% (volume / volume (v/v)) NCTC-109 medium (GIBCO, Grand Island, NY, U.S.A.), 15% (v/v) distilled water and 10% (v/v) fetal bovine serum (GIBCO) (17,20,23,24). The normal solution contained (in mM) 120 NaCl, 3.5 KCl, 1 CaCl 2 , 1 MgCl 2 , and 10 HEPES adjusted to pH 7.4 with NaOH.…”
mentioning
confidence: 99%
“…In A6 cell monolayers, hypotonic stress induces Na ϩ transport immediately (within 10 min) after application of the stress (18,24,26,27,29,37). Several studies revealed that hypotonic stress has a genomic and a nongenomic impact on Na ϩ reabsorption (26,29,33,37).…”
mentioning
confidence: 99%
“…Several studies revealed that hypotonic stress has a genomic and a nongenomic impact on Na ϩ reabsorption (26,29,33,37). We previously reported that the rapid, nongenomic effect of hypotonic stress on Na ϩ reabsorption is mediated through ligand-independent activation of receptortype tyrosine kinases (RTKs), such as epidermal growth factor receptor and platelet-derived growth factor receptor (37).…”
mentioning
confidence: 99%
“…In general, reports of increases in ␣-ENaC protein abundance are associated with elevations in ␣-ENaC transcript (1,14,15). However, in the A6 model of the renal collecting duct, hypotonicty is known to 1) increase transepithelial sodium transport without an increase the ENaC protein levels (20) and 2) increase the abundance of ␣-ENaC transcript (19). These effects of hypotonicity on ENaC regulation may be particularly relevant in the context of mouse models with chronic concentrating defects.…”
Section: Discussionmentioning
confidence: 99%